President Xi Jinping in the World and Regional Order and rethinking the Nepal-China Relations - Chakra Bam (Interdisciplinary Journal of Management and Social Sciences, 2024)
The leader of ambitious, President Xi Jinping, has developed their goodwill relations both in the world and regional order. Hence, under the Xi Jinping leadership, Nepal-China bilateral relations are deliberate friendly relationships with cordial manners. Therefore, in the words of American scholar Mark Borthwick, the twenty-first century was dubbed the “Pacific Century,” implying that the center of the world’s political and economic arena had shifted from the Atlantic to the Pacific. For this, Nepal has strengthened their South-North neighbor’s relations with equidistance and cordial position and boosted its interest. Currently, the BRI connectivity and cooperation incorporated Nepal-China relations and initiated Nepal’s economic prosperity. The old-aged relations initiated as a new height after President Xi’s leadership. In his period of Nepal-China, more than 33 high-level visits have been made, while over the two dozen agreements, MoUs were exchanged and treaties were signed. Under the ambitious mega-project of BRI, 64 cooperation and connectivity projects were agreed upon by Nepal and China. Besides this, 35 were on the economic corridor, 14 on multilateral initiative (now revised nine), and 15 on other relevant efforts. However, the MoUs on transit connectivity of the Kyirung-Kathmandu railway changed the dimension of Nepal-China relations with a new approach of landlocked to the railway linked in the trans-Himalayan region. Twenty-three years later, after President Jiang Zemin, President Xi started Nepal’s visit with new bilateral cooperation and a longstanding relationship. Methodologically, it is based on the secondary sources of data to analyze the Nepal-China relation from the perspective of Xi Leadership both in global and regional order, i.e., south Asia. Thus, closeness with Nepal, BRI, and Xi Jinping Thought incorporates Nepal’s political, economic, military assistance, and another dimension to enhance the Nepal-China relationship within prosperous and win-win situations. Therefore, one-China policy commitment is a significant factor for enhancing Nepal-China relations.